La substancia de Spinoza en la ﬁlosofía de la naturaleza de Schelling (2018)
In this article the inﬂuence of Baruch Spinoza in some aspects of the Philosophy of nature by F. Schelling is analyzed. The thesis tried to defend is that, although Schelling criticizes the substance of Spinoza, he also recognizes some positions of Spinozism and incorporates them in certain key aspects of his own philosophy. In particular, the article tries to show the reception of the spinozist substance in the Philosophy of nature.